SIBLINGS WITH ALLERGIC ANGIOEDEMA: A CASE SERIES ON ORAL ALLERGIC SYNDROME AND FAMILIAL ATOPY - Firstine Kelsi Hartanto; Jeff Jeff Tjokro; Vivi Angelina; Maria Leny Raiyon (FKG ULM, 2025)
Background: Oral Allergy Syndrome (OAS) is a localized IgE-mediated food allergy triggered by certain fruits and vegetables in patients with atopic history. This case report describes two siblings with Oral Allergy Syndrome (OAS) presenting as allergic angioedema triggered by specific food allergens. Case Presentation: Case 1 involves a 25-year-old female who developed lip swelling, a burning sensation, numbness, multiple oral ulcers on the lower lip, and surrounding redness 30 minutes after consuming mint sauce in an Indian dish. Case 2 details a 21-year-old male who experienced immediate lip and soft palate swelling with numbness after eating Chinese food suspected to contain nuts. Discussion: Both siblings share a history of childhood atopy, predisposing them to IgE-mediated reactions. Their symptoms were characteristic of localized allergic responses in the oral mucosa, consistent with OAS. Case Management: Management involved a combined therapeutic approach: topical corticosteroids were applied to the affected oral areas to reduce local inflammation and promote healing of the mucosal lesions, while oral corticosteroids provided systemic anti-inflammatory effects. Additionally, cetirizine, an H1 receptor antagonist, was administered to block histamine-mediated symptoms such as swelling and itching. Patients were also advised to avoid mint-containing and peanut-containing foods as predisposing factors. Conclusion: This report highlights not only the clinical presentation and successful management of OAS in individuals with familial atopy but also underscores the potential genetic predisposition contributing to food-induced allergic reactions.